Entre «Un oscuro día de justicia» y la «Carta abierta de un escritor a la Junta Militar» - Ronsino, Hernán (Facultad de Periodismo y Comunicación Social, 2017)
This article discusses two texts of Rodolfo Walsh’s work: «Carta abierta de un escritor a la Junta Militar» (1977) and the story «Un oscuro día de justicia» (1967). The main hypothesis of the author is that the first, written by Walsh days before being disappeared by the last Argentine military civic dictatorship, is the strongest bet of this intellectual to find other ways of narrating. After establishing the similarities and differences between the letter and the story, the article points out that both productions are a cry for help: in the fiction story the aid is expected to come by an external savior; in the last days of his life Walsh knows that liberation must come from the people themselves.